Overview of Community Perceptions on Mental Health and Mental Disorders in The Working Area of Kedurus Public Health Center - Lobis, Keizya Daniswara; Elsa Diandra Putri; Sukmawati, Sang Ayu Putu Wulan; Ersa Revida Athoilla; Mutiara Adiyana (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Mental health is a crucial element of overall well-being; however, public awareness and understanding of mental disorders remain inadequate in many communities, particularly in low-resource settings. This study explores community perceptions of mental health and mental illness among patients visiting the Kedurus Public Health Center (Puskesmas Kedurus) in Surabaya. Using a descriptive quantitative approach, a total of 60 respondents were selected via purposive sampling. Data were collected through structured questionnaires based on national mental health literacy indicators and analyzed using descriptive statistics. Results showed that more than 60% of participants demonstrated limited knowledge of early symptoms of mental illness, while approximately 70% exhibited negative attitudes or stigmatizing views toward individuals with mental disorders. Only around 30% recognized mental health as an essential part of daily well-being. These attitudes were shaped by cultural norms, insufficient public education, and restricted access to reliable mental health information. The findings underscore the need for sustained mental health education and stigma-reduction efforts at the primary care level. Community-based strategies, particularly those involving local leaders, may improve mental health literacy and foster a more supportive environment for individuals experiencing mental illness.